Role of sympathetic innervation in obesity - Pereira, Mafalda Maria Robalo de Azevedo Aleixo (2015)
Part of the results presented in this thesis were published in the following reference (DOI 10.1016/j.cell.2015.08.055): Wenwen Zeng*, Roksana M. Pirzgalska*, Mafalda M.A. Pereira, Nadiya Kubasova, Andreia Barateiro, Elsa Seixas, Yi-Hsueh Lu, Albina Kozlova, Henning Voss, Gabriel G. Martins, Jeffrey M. Friedman and Ana I. Domingos. Sympathetic Neuro-adipose Connections Mediate Leptin-Driven Lipolysis. Cell 163, 84-94 (2015). The work was also presented through poster presentations at iMED Conference 6.0 (Lisbon, 2014), Sociedade Portuguesa de Bioquímica Meeting (Coimbra, 2014) and Sociedade Portuguesa de Neurociências Meeting (Póvoa de Varzim, 2015).